2018
DOI: 10.1080/24750573.2018.1452521
|View full text |Cite
|
Sign up to set email alerts
|

Childhood trauma: a risk for major depression in patients with psoriasis

Abstract: INTRODUCTION:A history of childhood trauma is an important determinant for understanding the development of psychiatric and physical disorders. The chronic inflammatory disease, psoriasis, has been reported to be affected by childhood psychological stressors. Early life stress is also a well-known contributor to major depression. The current study aims to clarify a possible association between levels and types of childhood trauma with psoriasis severity and major depression. METHOD: Sixty-four patients diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 54 publications
1
12
0
Order By: Relevance
“…This is in line with existing evidence confirming a relationship between retrospectively reported childhood experiences and psoriasis ( 14 16 , 54 ). The severity of psoriasis was not correlated with traumatic experiences which is in line with Simonic et al ( 14 ) but contradicts other findings ( 55 ). The latter study also applied the CTQ and could show lower values than in our present sample (especially on the subscale sexual abuse).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This is in line with existing evidence confirming a relationship between retrospectively reported childhood experiences and psoriasis ( 14 16 , 54 ). The severity of psoriasis was not correlated with traumatic experiences which is in line with Simonic et al ( 14 ) but contradicts other findings ( 55 ). The latter study also applied the CTQ and could show lower values than in our present sample (especially on the subscale sexual abuse).…”
Section: Discussionsupporting
confidence: 81%
“…The latter study also applied the CTQ and could show lower values than in our present sample (especially on the subscale sexual abuse). The differences may be explained by peculiarities in the patient sample ( 55 ). The above mentioned study excluded PSO with a history of any psychiatric disorders and only patients from an outpatient clinic were enrolled.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with reports of a higher impact of tinnitus, hyperacusis-induced anxiety, and depression symptoms among patients who reported that during their first 18 years of life their parent(s) suffered from a mental illness ( Aazh et al, 2018 , 2019a , c , 2020 ). Mounting evidence suggests that adverse childhood experiences play a major lifelong role in mental and physical problems ( Anda et al, 2006 , 2010 ; Erfanian, 2018 ). Parental mental illness is an important form of adverse childhood experiences ( Anda et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…For some, this sense of underachieving resulted from a disruption to psychosexual maturation in adolescence lasting into early adulthood with negative beliefs about self/desirability being maintained in later life. 19,20 The complexities of backgrounds influenced anger, with the trauma reported in this study being similarly found in psoriasis 7,10,11 and other autoimmune conditions. 47 Participants perceived that anger caused by trauma had negatively impacted their health and contributed to both the onset and progression of psoriasis, suggesting that the challenges of living with psoriasis could serve as a secondary trauma.…”
Section: Discussionmentioning
confidence: 59%
“…Although psoriasis is an autoimmune condition, it is multifactorial in expression 3,4 as emotional life events can influence onset and clinical course. Research has focussed on the role of emotions 5,6 and stressful or traumatic life events triggering psoriasis 7–9 ; however, studies have reported mixed findings 10–12 . As such, questions remain about the role of emotions and experiences, their relationship with symptom severity, and the mechanisms of which trauma may interact with inflammatory markers 13 .…”
Section: Introductionmentioning
confidence: 99%